Drought erodes mountain plant community resistance to novel species under a warming climate - Max A. Schuchardt; Bernd J. Berauer; Justyna Giejsztowt; Andreas V. Heßberg; Yujie Niu; Michael Bahn; Anke Jentsch (Arctic, Antarctic, and Alpine Research, 2023)
Warming in mountain regions is projected to occur three times faster than the global average. Recently, a small number of observational studies have reported species loss in mountain plant communities and have explored mechanisms facilitating the colonization by novel species. We monitored translocated mountain plant communities and their novel competitor interactions following five years of exposure to downslope climates. We found increasing species turnover under two future climate scenarios with time. Local loss of native species was followed by the colonization by novel species after a severe drought year in the third year after translocation. Here, the assumed mechanism facilitating novel species colonization in mountain communities is direct environmental filtering. We find a time lag between the local loss of native species and the colonization by novel species, which can be explained by interacting climate stressors—that is, warming and drought—pushing communities across a threshold of resistance to colonization. Interestingly, despite significant changes in species identity and strong colonization by novel species, the proportional contribution of plant functional groups to aboveground biomass stayed stable across both sites of origin and over time. Our study provides experimental evidence of local species loss in mountain plant communities prone to severe climatic change, revealing abrupt threshold dynamics.